Networked Digital Technologies Second International Conference, NDT 2010, Prague, Czech Republic, July 7-9, 2010. Proceedings, Part I - Zavoral, Filip; Yaghob, Jakub; Pichappan, Pit.; El-Qawasmeh, Eyas.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the Second International Conference on Networked Digital Technologies, held in Prague, Czech Republic, in July 2010.
Information and Data Management -- A New Approach for Fingerprint Matching Using Logic Synthesis -- Extracting Fuzzy Rules to Classify Motor Imagery Based on a Neural Network with Weighted Fuzzy Membership Functions -- Distributed Data-Mining in the LISp-Miner System Using Techila Grid -- Non-negative Matrix Factorization on GPU -- Chatbot Enhanced Algorithms: A Case Study on Implementation in Bahasa Malaysia Human Language -- Handwritten Digits Recognition Based on Swarm Optimization Methods -- A Framework of Dashboard System for Higher Education Using Graph-Based Visualization Technique -- An Efficient Indexing and Compressing Scheme for XML Query Processing -- Development of a New Compression Scheme -- Compression of Layered Documents -- Classifier Hypothesis Generation Using Visual Analysis Methods -- Exploiting Punctuations along with Sliding Windows to Optimize STREAM Data Manager -- A Framework for In-House Prediction Markets -- Road Region Extraction Based on Motion Information and Seeded Region Growing for Foreground Detection -- Process Mining Approach to Promote Business Intelligence in Iranian Detectives$1 (BPolice -- Copyright Protection of Relational Database Systems -- Resolving Semantic Interoperability Challenges in XML Schema Matching -- Some Results in Bipolar-Valued Fuzzy BCK/BCI-Algebras -- Security -- The Effect of Attentiveness on Information Security -- A Secured Mobile Payment Model for Developing Markets -- Security Mapping to Enhance Matching Fine-Grained Security Policies -- Implementation and Evaluation of Fast Parallel Packet Filters on a Cell Processor -- On the Algebraic Expression of the AES S-Box Like S-Boxes -- Student$1 (Bs Polls for Teaching Quality Evaluation as an Electronic Voting System -- An Improved Estimation of the RSA Quantum Breaking Success Rate -- Mining Bluetooth Attacks in Smart Phones -- Users$1 (BAcceptance of Secure Biometrics Authentication System: Reliability and Validate of an Extended UTAUT Model -- Two Dimensional Labelled Security Model with Partially Trusted Subjects and Its Enforcement Using SELinux DTE Mechanism -- A Roaming-Based Anonymous Authentication Scheme in Multi-domains Vehicular Networks -- Human Authentication Using FingerIris Algorithm Based on Statistical Approach -- Aerial Threat Perception Architecture Using Data Mining -- Payload Encoding for Secure Extraction Process in Multiple Frequency Domain Steganography -- An Implementation of Digital Image Watermarking Based on Particle Swarm Optimization -- Genetic Cryptanalysis -- Multiple Layer Reversible Images Watermarking Using Enhancement of Difference Expansion Techniques -- Modeling and Analysis of Reconfigurable Systems Using Flexible Nets -- Using Privilege Chain for Access Control and Trustiness of Resources in Cloud Computing -- Social Networks -- Modeling of Trust to Provide Users Assisted Secure Actions in Online Communities -- A Collaborative Social Decision Model for Digital Content Credibility Improvement -- Improving Similarity-Based Methods for Information Propagation on Social Networks -- Approaches to Privacy Protection in Location-Based Services -- Social Media as Means for Company Communication and Service Design -- A Problem-Centered Collaborative Tutoring System for Teachers Lifelong Learning: Knowledge Sharing to Solve Practical Professional Problems -- Bridging the Gap between Web 2.0 Technologies and Social Computing Principles -- Ontology -- Using Similarity Values for Ontology Matching in the Grid -- Rapid Creation and Deployment of Communities of Interest Using the CMap Ontology Editor and the KAoS Policy Services Framework -- Incorporating Semantics into an Intelligent Clothes Search System Using Ontology -- SPPODL: Semantic Peer Profile Based on Ontology and Description Logic -- Ontology Based Tracking and Propagation of Provenance Metadata -- Real Time Biometric Solutions for Networked Society -- A Real-Time In-Air Signature Biometric Technique Using a Mobile Device Embedding an Accelerometer -- On-Demand Biometric Authentication of Computer Users Using Brain Waves -- Encrypting Fingerprint Minutiae Templates by Random Quantization -- Web Applications -- Method for Countering Social Bookmarking Pollution Using User Similarities -- A Human Readable Platform Independent Domain Specific Language for WSDL -- A Human Readable Platform Independent Domain Specific Language for BPEL -- Impact of the Multimedia Traffic Sources in a Network Node Using FIFO scheduler -- Assessing the LCC Websites Quality -- Expediency Heuristic in University Conference Webpage.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Software Engineering; Database Management